2017
DOI: 10.1021/acsinfecdis.7b00020
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming an Extremely Drug Resistant (XDR) Pathogen: Avibactam Restores Susceptibility to Ceftazidime for Burkholderia cepacia Complex Isolates from Cystic Fibrosis Patients

Abstract: Burkholderia multivorans is a significant health threat to persons with cystic fibrosis (CF). Infections are difficult to treat as this pathogen is inherently resistant to multiple antibiotics. Susceptibility testing of isolates obtained from CF respiratory cultures revealed that single agents selected from different antibiotic classes were unable to inhibit growth. However, all isolates were found to be susceptible to ceftazidime when combined with the novel non-β-lactam β-lactamase inhibitor, avibactam (all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 29 publications
5
66
0
1
Order By: Relevance
“…However, there is a lack of knowledge of its activity against MDRO recovered in CF, 3 although it has shown an in vitro activity against some strains of Burkholderia spp. 4,5 We assessed in vitro susceptibility of 30 S. maltophilia, 30…”
Section: Trends In Ceftazidime-avibactam Activity Against Multidrug-rmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a lack of knowledge of its activity against MDRO recovered in CF, 3 although it has shown an in vitro activity against some strains of Burkholderia spp. 4,5 We assessed in vitro susceptibility of 30 S. maltophilia, 30…”
Section: Trends In Ceftazidime-avibactam Activity Against Multidrug-rmentioning
confidence: 99%
“…1,2 Ceftazidime-avibactam is a new cephalosporin-inhibitor combination with a potent activity against multidrug-resistant organisms (MDRO) such as KPC and OXA-48 like producing Enterobacteriacae and multidrug resistant P. aeruginosa.However, there is a lack of knowledge of its activity against MDRO recovered in CF, 3 although it has shown an in vitro activity against some strains of Burkholderia spp. 4,5 We assessed in vitro susceptibility of 30 S. maltophilia, 30Achromobacter spp and 13 Bcc isolates to ceftazidime-avibactam by e-tests and to other antibiotics by the disc diffusion method or e-tests. Clinical isolates recovered from respiratory samples were identified by MALDI-TOF mass spectrometry (Microflex LT with the Compass database, Bruker, Germany).…”
mentioning
confidence: 99%
“…Papp‐Wallace et al found that when avibactam was combined with ceftazidime, susceptibility to ceftazidime in MDR and XDR clinical strains of Burkholderia spp isolated from CF respiratory specimens was restored. To the best of our knowledge, the synergism between ceftazidime/avibactam and meropenem against BCC has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Pen A has a very broad substrate profile that includes carbapenems and β‐lactamase inhibitors. Avibactam was shown to be a potent inhibitor of the Pen A . CAZ‐AVI has an antimicrobial spectrum of activity including MDR GNB, consequently it may improve the outcomes of patients infected with those pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Non β‐lactamase‐mediated resistance, like efflux pumps and reduced outer membrane permeability, also plays a role in the decreased susceptibility of Bcc species toward beta lactam antibiotics . Avibactam is a novel β‐lactamase inhibitor which contrasts the activities of Ambler class A‐serine, C‐serine β‐lactamases and some Ambler class D‐serine enzymes (OXA‐48) to restore the susceptibility to ceftazidime by preventing enzymatic hydrolysis without changing the Class B‐MBL . The combination of ceftazidime/avibactam (CAZ‐AVI) represents a novel therapeutic option for Bcc, due to much higher in vitro susceptibility than ceftazidime alone .…”
Section: Introductionmentioning
confidence: 99%